If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(8x + -14) = 492 Reorder the terms: 6(-14 + 8x) = 492 (-14 * 6 + 8x * 6) = 492 (-84 + 48x) = 492 Solving -84 + 48x = 492 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '84' to each side of the equation. -84 + 84 + 48x = 492 + 84 Combine like terms: -84 + 84 = 0 0 + 48x = 492 + 84 48x = 492 + 84 Combine like terms: 492 + 84 = 576 48x = 576 Divide each side by '48'. x = 12 Simplifying x = 12
| 3x^2-12x+2x-8=0 | | x/20+7x/12=x/8 | | x^2+12=-3x | | 7(u-7)-3=-6(-4u+8)-9u | | -52=-2(m+4)+6m | | 7n-1=12 | | (9-2y)=5(2-3y)-50 | | .08*x+.06(1500-x)=106.40 | | x-(x-8)=x-3 | | -2[7-n]+4= | | a^2-5b+9=0 | | 1/6(5x-3)=4 | | j+19=43 | | 4[8n+2]= | | h=4b | | 18-6= | | 6-18= | | Y/5=10 | | 8/5x=24 | | 4a+1/2=10 | | 9(7x-10)=351 | | 5x^4-20x^3+20x^2=0 | | 12x-276=3x-6 | | 12x^2+1x=6 | | 3x+7=4x(-3x) | | 4z+6=18 | | 4x-4=8(x-1) | | 6(12-12x)+7(2+15x)=105 | | 214-2x=43x+19 | | 3a-a= | | 4*bfc=6 | | 3*g=65435 |